Area-wide soil parameters of the germanic-roman battlefield site Harzhorn, Northeim (Lower Saxony, Germany) - Jacob Hardt; Ben McLeod; Lena Schimmel; Lena Rißmann; Norbert Anselm; Linda Kaeser; Manuela Abendroth; Torben Schatte; Petra Lönne; Michael Geschwinde; Michael Meyer; Philipp Hoelzmann (PANGAEA, 2021)
Within the framework of the DFG-funded project Archaeological and geoarchaeological investigations at the germanic-roman battlefield site Harzhorn (Northeim, Lower Saxony, Germany), more than 630 samples of the topsoil were taken in relatively high spatial density in order to investigate the relationship between soil parameters and the conservation status of iron objects. The Harzhorn incident took place around the year 235 CE on a Muschelkalk ridge (Harzhorn site) and a neighbouring hill (Kahlberg site) consisting of Jurassic limestone. Upper Buntsandstein and Quaternary loess also occur in some areas. During previous archaeological excavations, the very heterogenuous preservation of iron finds, such as arrow heads, pilae, or shoe nails, was noticed and a correlation with the surface geology/soil properties was assumed. In order to investigate into this relationship, soil samples were taken across the areas at a relatively high density. The sampling was carried out in 2018, the laboratory analyses in the Laboratory for Physical Geography of the Institute for Geographical Sciences at Freie Universität Berlin were finished in 2019. At the Harzhorn site, the vast majority of archaeological finds were discovered at a depth between 15 - 20 cm. As we were interested in the area-wide in situ soil conditions to evaluate the soil aggressiveness, the soil samples at the Harzhorn site were taken at a depth of 15 cm. At the Kahlberg site, the vast majority of archaeological finds were discovered at a depth between 25 - 30 cm. Thus, at the Kahlberg site the soil samples were taken at a depth of 25 cm. Additionally, in the course of archaeological excavations, we sampled 8 profiles at different depths at the Kahlberg site. All samples were analysed with regard to: pH value (Hanna instruments pH meter, measured in KCl), Electric conductivity (Hanna instruments EC meter, measured in distilled water), and loss on ignition (550°C + 880°C). On a selected number of samples grain size analyses were carried out (laser particle sizer LS 13320 PIDS Beckman Coulter).